Missed Opportunities for the Diagnosis of Colorectal Cancer - Siminoff, Laura A. (Biomed Res Int, 2015)
Objective. To examine patient and medical characteristics which predict a missed diagnostic opportunity (MDO) for colorectal cancer (CRC). Methods. The sample consisted of 252 patients diagnosed with Stages 1–4 CRC who were diagnosed in the prior six months, had experienced symptoms prior to diagnosis, and were not diagnosed through routine screening. Systematic review of all medical records prior to patients' diagnosis was conducted. An MDO was defined as a clinical encounter where, even in the presence of presumptive CRC symptoms, the CRC diagnostic process is not started. Results. 92 patients (36.5%) experienced an MDO. Almost 80% of alternate diagnoses were other GI-GU diseases, including hemorrhoids and diverticulitis. Stomach pain, anemia, and constipation were the most common symptoms experienced by the MDO group. These symptoms, and weight loss and vomiting, were more likely to be noted in the charts of the MDO patients (P < 0.04). Independent risk factors for MDO included age (<50) [OR = 2.29 (1.14–4.60), P = 0.02] and female sex [OR = 2.19 (1.16–4.16), P = 0.03]. Each additional physician seen, more than doubled the MDO risk [OR = 2.05 (1.53–2.74), P < 0.001]. Conclusions. Females, younger patients, and those consulting more physicians were all more likely to experience an MDO. Continued increased training of physicians to enhance knowledge of who is vulnerable to CRC is needed in addition to an increased focus to adherence to screening recommendations.